2021
DOI: 10.1016/j.breast.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes tumors of the breast: Adjuvant radiation therapy revisited

Abstract: Background Phyllodes tumors (PT) are rare entity and surgical resection is the cornerstone of treatment. No standard of care exists regarding adjuvant treatment especially radiation therapy (RT). Patients and methods We analyzed all patients with non-metastatic, resected phyllodes tumors who presented to our institution from January 2005 through December 2019. Primary study endpoints included local recurrence free survival (LRFS) and overall survival (OS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The NCCN recommends consideration of adjuvant radiotherapy for recurrent PT, and a recent study reported significantly improved local recurrence-free survival in patients with borderline and malignant PT treated with adjuvant radiation following wide local excision to negative margins. 18 Our study is limited by small sample size. Although all available data were included, dating back to the inception of our institutional pathology database, PT has a low incidence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The NCCN recommends consideration of adjuvant radiotherapy for recurrent PT, and a recent study reported significantly improved local recurrence-free survival in patients with borderline and malignant PT treated with adjuvant radiation following wide local excision to negative margins. 18 Our study is limited by small sample size. Although all available data were included, dating back to the inception of our institutional pathology database, PT has a low incidence.…”
Section: Discussionmentioning
confidence: 91%
“…The NCCN recommends consideration of adjuvant radiotherapy for recurrent PT, and a recent study reported significantly improved local recurrence-free survival in patients with borderline and malignant PT treated with adjuvant radiation following wide local excision to negative margins. 18…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al showed that adjuvant RT for borderline/malignant PT decreased the LR rate in patients undergoing BCS (50). However, Boutrus et al showed that RT was not suitable for BPT but may improve local recurrence free survival for borderline/malignant PT (52). We did not assess RT as a risk factor due to the limited data and more data are needed for further exploration of this issue.…”
Section: Respectively (P=0397) Second International Consensusmentioning
confidence: 97%
“…In the absence of a standard of care regarding adjuvant treatment, surgical resection is the cornerstone of their treatment. Regardless, the therapy should be multidisciplinary and possibly managed by a specialized center [156][157][158].…”
Section: Margin Acceptability In the Case Of Non-epithelial Malignanciesmentioning
confidence: 99%